The Effects of Ultrasound-Guided Transversus Abdominis Plane Block on Acute and Chronic Postsurgical Pain After Robotic Partial Nephrectomy: A Prospective Randomized Clinical Trial. Issue 2 (29th August 2019) - Covotta, Marco; Claroni, Claudia; Costantini, Manuela; Torregiani, Giulia; Pelagalli, Lorella; Zinilli, Antonio; Forastiere, Ester
Abstract: Background: Use of a locoregional analgesia technique, such as the ultrasound-guided transversus abdominis plane block (TAPb), can improve postoperative pain management. We investigated the role of TAPb in robotic partial nephrectomy, a surgery burdened by severe postoperative pain. Methods: In this prospective trial, patients with American Society of Anesthesiologists class I–III physical status undergoing robotic partial nephrectomy were randomly assigned to standard general anesthetic plus ultrasound-guided TAPb (TAP group) or sole standard general anesthetic (NO-TAP group). The primary end point was morphine consumption 24 hours after surgery. Secondary outcomes were postoperative nausea and vomiting in the first 24 hours, sensitivity, and acute and chronic pain, as measured by multiple indicators. Results: A total of 96 patients were evaluated: 48 patients in the TAP group and 48 in the NO-TAP group. Median morphine consumption after 24 hours was higher in the NO-TAP group compared with the TAP group (14.1 ± 4.5 mg vs 10.6 ± 4.6, P  < 0.008). The intensity of acute somatic pain and the presence of chronic pain at three and six months were higher in the NO-TAP group. Conclusions: Our results show that TAPb can significantly reduce morphine consumption and somatic pain, but not visceral pain. TAPb reduced the incidence of chronic pain.